1998
DOI: 10.1002/(sici)1521-4117(199804)15:2<81::aid-ppsc81>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mass Flux Measurements in Sprays using a Patternator and the Phase-Doppler Technique

Abstract: The phase-Doppler technique (PDA) has become one of the most important instrumental methods in two-phase flow research in recent years because of its capability of simultaneously determining the diameter and velocity of spherical particles. However, the shortcomings of this technique with respect to volume flux measurement have become increasingly apparent. In order to study the performance of different PDA instruments, comparative flux measurements in two characteristic sprays using a patternator and three ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In the first configuration, the detectors were located outside of the plane defined by the incident laser beams; conversely, in the second one the detectors were located in the same plane as the incident beams. This design was developed to improve measurement accuracy of liquid volume flux [14].…”
Section: Optical Diagnosticmentioning
confidence: 99%
“…In the first configuration, the detectors were located outside of the plane defined by the incident laser beams; conversely, in the second one the detectors were located in the same plane as the incident beams. This design was developed to improve measurement accuracy of liquid volume flux [14].…”
Section: Optical Diagnosticmentioning
confidence: 99%
“…As can be seen from Figure 4, the PDI was able to detect mass from 1 to 5 m away from the sprayer; however string data have yet to be processed to correlate these procedures. A common limitation for all phase Doppler measures is the sampling frequency whereas >10,000 counts are needed for statistical validity (Dullenkopf et al, 1998;Nuyttens, Baetens, De Schampheleire, & Sonck, 2007;Parkin, 1993;Tratnig & Brenn, 2010). The current experiment only observed 2 to 491 counts.…”
Section: In-field Investigation Of Pdi Versus Stringsmentioning
confidence: 55%
“…This does not indicate that 85% of the data were missing, but that the spray plume was in the sampling area of the pD interferometer for ≥15% of the time. Similarly, Dullenkopf et al (1998) found that time-sequence data obtained in a laboratory patternation assessment using a similar pD device contained up to 5% gaps.…”
Section: Discussionmentioning
confidence: 83%